PENYUSUNAN BAHAN AJAR BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) UNTUK PEBELAJAR ANAK - Syarifah Lubna (Balai Bahasa Kalimantan Barat, 2017)
BIPA development could not be separated from the material development. Teaching materials are also needed in every learning process and every level of education. During this time, the preparation of teaching materials and manufacturing is focused in an effort to introduce Indonesian culture is intended for adult level foreign speakers. The child learners also need special attention since many institutions also teaches Indonesian language to children. The focus of this paper is to provide sample materials aimed at teaching Indonesian for Foreign Speakers (BIPA) for children. The materials presented are materials that match the characteristics of children young learners. Preparation of material well adapted to the principles of materials development for children who should be full of images and colors to attract more children to learn the language.